1998
DOI: 10.1086/305251
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Radio Galaxy in Abell 428: A Large, Powerful FR I Source in a Disk‐dominated Host

Abstract: We report the discovery of a powerful (∼ 10 24 h −2 75 W Hz −1 at 20cm) FR I radio source in a highly flattened disk-dominated galaxy. Half of the radio flux from this source is concentrated within the host galaxy, with the remainder in a pair of nearly symmetrical lobes with total extent ∼ 200 kpc nearly perpendicular to the disk. The traditional wisdom maintains that powerful, extended radio sources are found only in ellipticals or recent merger events. We report B, R, J, and K imaging, optical spectroscopy,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 70 publications
3
66
0
Order By: Relevance
“…The discovery of the spiral-host radio galaxy 0313-192 was reported in Ledlow et al (1998), Ledlow et al (2001). Here, we present new images (see also: Keel et al (2002)) from HST and Gemini, illustrating beyond doubt the spiral (Sa/Sb) nature of the host and clearly showing a warped disk.…”
Section: A Unique Spiral Radio Galaxysupporting
confidence: 50%
“…The discovery of the spiral-host radio galaxy 0313-192 was reported in Ledlow et al (1998), Ledlow et al (2001). Here, we present new images (see also: Keel et al (2002)) from HST and Gemini, illustrating beyond doubt the spiral (Sa/Sb) nature of the host and clearly showing a warped disk.…”
Section: A Unique Spiral Radio Galaxysupporting
confidence: 50%
“…For example, J031552-190644 is known to have a spiral host galaxy (Ledlow et al 1998) and found to have Hi gas by Ledlow et al (2001) within a galactic disc. However, the WISE data indicate that this galaxy lies in the Figure 7.…”
Section: Mid-infrared Colour Informationmentioning
confidence: 99%
“…Table 1 gives a complete-to-date list of spiral galaxies that host large double-lobed radio sources 1 . 0313-192 was the first confirmed doublelobed radio source hosted by a spiral galaxy (Ledlow, Owen, & Keel 1998;Ledlow et al 2001;Keel et al 2006) 2 . 0313-192 is an edge-on spiral galaxy (Hubble type Sb) that hosts a 360 kpc double-lobed radio source.…”
Section: Radio Galaxies That Are Hosted By Spiralsmentioning
confidence: 99%